1995
DOI: 10.1083/jcb.130.2.451
|View full text |Cite
|
Sign up to set email alerts
|

CD31/PECAM-1 is a ligand for alpha v beta 3 integrin involved in adhesion of leukocytes to endothelium.

Abstract: Abstract. To protect the body efficiently from infectious organisms, leukocytes circulate as nonadherent cells in the blood and lymph, and migrate as adherent cells into tissues. Circulating leukocytes in the blood have first to adhere to and then to cross the endothelial lining. CD31/PECAM-1 is an adhesion molecule expressed by vascular endothelial cells, platelets, monocytes, neutrophils, and naive T lymphocytes. It is a transmembrane glycoprotein of the immunoglobulin gene superfamily (IgSF), with six Ig-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
192
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 352 publications
(198 citation statements)
references
References 82 publications
5
192
0
1
Order By: Relevance
“…36 In addition, it has been suggested that PECAM-1 can interact with upregulated ␣ v ␤ 3 . 37,38 In the present study, a significant modulation of endothelial PECAM-1 expression, lining the whole vessel wall circumference, was observed for apoEdeficient but not wild-type mice. It is of interest to note that PECAM-1 expression can be significantly modulated after treatment of human umbilical vein endothelial cells with inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 62%
“…36 In addition, it has been suggested that PECAM-1 can interact with upregulated ␣ v ␤ 3 . 37,38 In the present study, a significant modulation of endothelial PECAM-1 expression, lining the whole vessel wall circumference, was observed for apoEdeficient but not wild-type mice. It is of interest to note that PECAM-1 expression can be significantly modulated after treatment of human umbilical vein endothelial cells with inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 62%
“…The unique structural homology of CD31's extracellular region is responsible for facilitating numerous heterophilic and homophilic binding interactions between differing vascular tissues (10,16). For example, CD31 is highly expressed in the border junctions of endothelial cells where it plays a role in endothelial cell motility and regulating leukocyte transendothelial migration (31). In CD31 knockout mice, endothelial cell motility and filopodia formation as well as neovascularization are markedly impaired (5).…”
mentioning
confidence: 99%
“…Apart from the T cell CD31 ligand (T-CD31L; Ref. 13), the proposed heterophilic counterreceptors of CD31 include a heparin-containing proteoglycan (16,17), the integrin ␣ v ␤ 3 (18,19), a molecule expressed by parasitized RBC (20), and the ADP-ribosyl cyclase CD38 (21).…”
mentioning
confidence: 99%